Kewirausahaan Sosial (Social Entrepreneurship) Mahasiswa Indonesia - Prawira Mahardika (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study discusses social entrepreneurship among Indonesian university students as a form of innovation in addressing social problems through an entrepreneurship approach that emphasizes social value creation. The purpose of this study is to understand the concepts, theories, and relevance of social entrepreneurship practices that develop among students, as well as to identify their contributions to social and economic development in society. The research method used is a qualitative approach with a literature study design. Data and information were obtained from scientific journals, books, research reports, and official documents relevant to the research topic. All data were analyzed using descriptive-narrative analysis techniques to describe patterns, trends, and important findings related to the object of study. The results show that social entrepreneurship among students has great potential to encourage creativity, leadership, and social awareness, and can serve as an alternative solution to various social problems such as poverty, unemployment, and limited access to education. In addition, the implementation of social entrepreneurship concepts contributes to shaping entrepreneurial character that is ethical, innovative, and oriented toward sustainability. This study is expected to serve as a reference for the development of social entrepreneurship education in higher education institutions.